CHARACTERISTICS OF THE TOURIST DISTRICT OF BUKHARA REGION - Primova Shahlo Dzhumaevna; Sharipov Jahongir Mirzo Anvarjon ugli (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides information on the principles of tourist zoning in the Bukhara region, the stages of tourist zoning.